2006
DOI: 10.1016/j.orl.2005.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Relaxations of linear programming problems with first order stochastic dominance constraints

Abstract: Linear stochastic programming problems with first order stochastic dominance (FSD) constraints are non-convex. For their mixed 0-1 linear programming formulation we present two convex relaxations based on second order stochastic dominance (SSD). We develop necessary and sufficient conditions for FSD, used to obtain a disjunctive programming formulation and to strengthen one of the SSD-based relaxations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…Condition (7) can be used to derive a MIP formulation for a first-order stochastic dominance (FSD) constraint [24,25]. W (1) Y if and only if there exists β such that…”
Section: Review Of Existing Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Condition (7) can be used to derive a MIP formulation for a first-order stochastic dominance (FSD) constraint [24,25]. W (1) Y if and only if there exists β such that…”
Section: Review Of Existing Resultsmentioning
confidence: 99%
“…In addition, the linear relaxation of this formulation is also a formulation of SSD. As a result, the linear programming relaxation of this formulation is equivalent to the SSD relaxation proposed in [24], and shown to be a tight relaxation of FSD in [25].…”
Section: E[h(w )] ≥ E[h(y )]mentioning
confidence: 99%
See 1 more Smart Citation
“…Because this formulation includes all the variables and constraints of the SSDLP formulation, the linear programming relaxation yields a bound at least as strong as the bound obtained from the SSD relaxation, relaxing the FSD constraint W 1 Y to an SSD constraint W 2 Y . For scalar stochastic dominance constraints it has been shown that the SSD relaxation is often good (Noyan et al, 2006). Furthermore, for an important special case in which W and Y take on all values with equal probability, we show in § 4.4 that the SSD relaxation is in a sense as good as can be achieved.…”
Section: Two Compact Mip Formulation (Fsd1 and Fsd1+ssd)mentioning
confidence: 62%
“…This fact leads to an LP relaxation which is different from the usual one obtained by relaxing the integrality restriction. In [28] we provide examples which show that neither of these relaxations is stronger than the other.…”
Section: Second Order Constraints As Valid Inequalitiesmentioning
confidence: 92%